2019
DOI: 10.14393/bj-v35n1a2019-41749
|View full text |Cite
|
Sign up to set email alerts
|

Production regions and physical quality of Urochloa decumbens CV. Basilisk seeds

Abstract: Brazil is the largest world producer, consumer and exporter of forage grass seeds. Urochloa decumbens Stapf. species is the second in importance in the Brazilian market of seeds of tropical forage grasses. Seeds are harvested by the soil sweeping method and, in addition to other impurities, harvested lots can present weed seeds, which makes seeds unfeasible for commercialization. The aim of the present study was to evaluate differences in the physical quality and viability of Urochloa decumbens cv. Basilisk se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…According to Pereira et al The only sample of U. decumbens showed physical purity below that established by legislation, with 41.6% (Figure 4). In a study by Silva et al (2019) approximately 33% of the U. decumbens production fields had seed lots with values below the standards established by the /Ministry of Agriculture for commercialization, with purity between 40.4 and 56.3%. According to Laura et al (2009), in general, this is the species of Urochloa with the lowest purity, with an average of 46.9%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Pereira et al The only sample of U. decumbens showed physical purity below that established by legislation, with 41.6% (Figure 4). In a study by Silva et al (2019) approximately 33% of the U. decumbens production fields had seed lots with values below the standards established by the /Ministry of Agriculture for commercialization, with purity between 40.4 and 56.3%. According to Laura et al (2009), in general, this is the species of Urochloa with the lowest purity, with an average of 46.9%.…”
Section: Resultsmentioning
confidence: 97%
“…The coating is an efficient technique for the initial establishment of pastures, facilitating the sowing operation in notillage systems (OLIVEIRA et al, 2003). Silva et al (2019) worked with 10 samples of the cultivar BRS Piatã of the U. brizantha species, coming from several Brazilian states, and observed that in 8 the physical purity was greater than the minimum value for commercialization established by the MAPA norms for the species. Barros Ribeiro et al (2016) also analyzed the same cultivar that was being marketed in Goiânia and found that it had the highest purity, with 96.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of precipitations during natural fall and harvesting may lead to deterioration and increase of the incidence of fungi in seeds and also impair the work of harvesting machines (MARCOS-FILHO, 2016;SOUZA, 2001). Thus, in the choice of seed production fields, priority should be given to sites that allow harvesting the field in drought periods (SILVA et al, 2019a). Table 2 presents the results of the physiological quality analysis of seeds that was also different among lots of production fields.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the conditions that favor production and quality of forage grass seeds allows the recognition of new areas with potential for the implantation of new production fields (MARCOS-FILHO, 2016;SILVA et al, 2019bc;). The selection of the best areas for the production of these seeds enables reducing costs through sectorization logistics, identification of producing areas and production of high-quality seeds (SILVA et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, embora diversos estudos avaliem a qualidade física e fisiológica de sementes de Urochloa (FRANÇA-NETO, 2009;FONTANELI et al, 2012;SILVA, 2013;CARDOSO et al, 2014;BATISTA et al, 2016;SILVA et al, 2019), gênero com maior produção de sementes pelo Brasil, avaliações referentes ao gênero Megathyrsus ainda são limitadas. Em um dos poucos estudos de lotes de capimcolonião, Ohlson et al (2010) avaliaram sementes do gênero comercializados no Estado do Paraná e verificaram que a maioria dos lotes não atendeu o padrão mínimo legal exigido quanto a pureza e que, neste caso, o teste de germinação não era nem realizado.…”
Section: Introductionunclassified